Models of multisectoral social policy towards older people and old age in the context of technological change - Klimczuk, Andrzej (Journal of Public Governance, 2015)
Ageing is a challenge that requires development and implementation of horizontal social policy, which should take into account the diversity of older adults and the division of interventions aimed at this population and on the image of old age. The complexity of the negative consequences of ageing shows that there is a need to enhance cooperation between the public sector, the commercial sector, the NGO sector, and the informal sector at all levels of social policy. The paper discusses models of multisectoral social policy and the possibilities of integrating social services. Its conclusions include directions for further research and social innovation.